High-speed ghost imaging by an unpredictable optical phased array - Sun, Xuyang; Chen, Hui; Qiu, Bingni; Wang, Gao; Xu, Wanting; Luo, Sheng; Yuan, Yuan; Chen, Bing; Zheng, Huaibin; He, Yuchen; Xu, Zhuo (Frontiers in Physics, 2022)
Ghost imaging (GI) retrieves an image from the correlation between a sequence of illumination patterns on the object and their corresponding bucket detections. Traditionally, GI requires the precise prediction of the illumination patterns, which raises technology barriers on building a high speed illumination source, limiting the scope of its application. We here propose a high speed GI system which implements a self-correlation with a purely optical operation without determining illumination patterns. The light source is an optical phased array (OPA), built of a set of waveguide-type electro-optic phase modulators. The OPA is driven to randomly change the phases in every 200 ns, generating speckle patterns at a rate of 5 MHz. Although the speckle patterns are unstable and unpredictable, with the help of the Naked-eye GI scheme, the system in real-time optically generates the images of the object at a frame rate of more than 1 kHz, which can be directly observed by eyes or a camera. This method avoids acquiring the information of the illumination, providing a simple and easy way to realize high speed GI. It also inspires a different way of applying OPAs to high speed imaging.